Anode for all-solid-state secondary battery and all-solid-state secondary battery

By adopting a double-layer negative electrode hybrid layer structure in an all-solid-state secondary battery, the adhesive content is adjusted to control the peel strength, the problem of unstable connection between the negative electrode current collector and the hybrid layer is solved, and the fast charging capacity and cycle life of the battery are improved.

JP2025019588APending Publication Date: 2025-02-07SAMSUNG SDI CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2023123271
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-28
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

In the existing all-solid-state secondary batteries, the peel strength between the negative electrode current collector and the negative electrode mixing layer is too large or too small, resulting in the negative electrode mixing layer being disengaged or position shifted, affecting battery performance, and short circuits and shortening of cycle life are prone to occur during fast charging.

Method used

A negative electrode mixed layer with a double-layer structure is adopted, wherein the first and second layers contain different adhesive contents, the first layer has a higher adhesive content than the second layer, and the peel strength is controlled between 35mN/mm and 490mN/mm to ensure a firm connection between the negative electrode current collector and the mixing layer.

Benefits of technology

Effectively reduce the risk of short circuit during fast charging, maintain battery capacity, and suppress battery performance attenuation during cyclic charging and discharging.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025019588000001_ABST
    Figure 2025019588000001_ABST
Patent Text Reader

Abstract

To provide a negative electrode for an all-solid-state secondary battery which is unlikely to cause a short circuit even when rapidly charged and which can maintain a high battery capacity even when the battery is repeatedly charged and discharged.SOLUTION: In an all-solid-state secondary battery negative electrode 20, a negative electrode mixture layer 22 includes a first layer 221 forming a surface of the negative electrode mixture layer facing a negative electrode current collector 21, and a second layer 222 forming a surface of the negative electrode mixture layer opposite the first layer, and the first layer and the second layer each contain a negative electrode active material, a carbon material, and a binder, and the binder content A in the first layer is 5 pts.mass or more and 20 pts.mass or less with respect to 100 pts.mass of the total content of the negative electrode active material and the carbon material in the first layer, and the binder content B in the second layer is 1 pt.mass or more and 10 pts.mass or less with respect to 100 pts.mass of the total content of the negative electrode active material and the carbon material in the second layer, the content A is greater than the content B, and the difference between the content A and the content B is in the range of 4 pts.mass or more and 19 pts.mass or less.SELECTED DRAWING: Figure 4
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a negative electrode for an all-solid-state secondary battery and an all-solid-state secondary battery including the negative electrode. [Background technology]

[0002] All-solid-state secondary batteries are expected to have a significantly improved energy density compared to conventional secondary batteries that use electrolytes. In addition, the demand for EVs has increased dramatically in recent years, making it urgent to establish technologies to improve rapid charging performance and suppress cycle degradation.

[0003] One of the factors that affect the battery performance of the above-mentioned all-solid-state secondary battery is the peel strength between the negative electrode current collector and the negative electrode mixture layer that constitute the electrode of the all-solid-state secondary battery.

[0004] If the peel strength between the negative electrode current collector and the negative electrode mixture layer is too small, the negative electrode mixture layer may peel off from the negative electrode current collector or the position of the negative electrode mixture layer may shift during the assembly process of the all-solid-state secondary battery, which may result in the negative electrode being unable to function as a negative electrode or causing a short circuit.

[0005] Therefore, as shown in Patent Documents 1 to 3, in order to increase the peel strength between the negative electrode current collector and the negative electrode mixture layer, the content of the binder in the negative electrode mixture layer is made relatively larger than that in other parts, thereby all-solid-state lithium secondary batteries have been devised in which the peel strength between the negative electrode current collector and the negative electrode mixture layer is increased. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] Korean Patent No. 2071585 [Patent Document 2] Korean Patent No. 2053063 [Patent Document 3] Korean Patent No. 1527748 Summary of the Invention [Problem to be solved by the invention]

[0007] However, as a result of intensive research by the present inventors, it was found that if the peel strength between the negative electrode current collector and the negative electrode mixture layer is too large, not only will the battery capacity be reduced, but cracks may occur in the negative electrode mixture layer when lithium is precipitated during charging. If a crack occurs in the negative electrode mixture layer, for example, lithium precipitated in the negative electrode may concentrate at the crack, causing a short circuit.

[0008] The present inventors further considered that not only the peel strength between the negative electrode current collector and the negative electrode mixture layer, but also the peel strength between the negative electrode mixture layer and the solid electrolyte layer is one of the factors that affect the performance of the all-solid-state battery. In this specification, the performance of the all-solid-state battery refers to the battery capacity and the suppression of short circuits during charging.

[0009] The present invention has been made in view of the above-mentioned problems, and has an object to provide a negative electrode for an all-solid-state secondary battery that is unlikely to cause a short circuit during rapid charging and can suppress cycle deterioration. [Means for solving the problem]

[0010] That is, the negative electrode for an all-solid-state secondary battery and the all-solid-state secondary battery according to the present invention are as follows. [1] A negative electrode for an all-solid-state secondary battery comprising a negative electrode current collector and a negative electrode mixture layer, the negative electrode mixture layer includes a first layer forming a surface of the negative electrode mixture layer facing the negative electrode current collector, and a second layer forming a surface opposite to the first layer, The first layer and the second layer each contain a negative electrode active material, a carbon material, and a binder, a content A of the binder in the first layer is 5 parts by mass or more and 20 parts by mass or less with respect to 100 parts by mass of the total mass of the negative electrode active material and the carbon material in the first layer, a content B of the binder in the second layer is 1 part by mass or more and 10 parts by mass or less with respect to 100 parts by mass of the total mass of the negative electrode active material and the carbon material in the second layer, a negative electrode for an all-solid-state secondary battery, wherein the content A is greater than the content B, and the difference between the content A and the content B is in the range of 4 parts by mass or more and 19 parts by mass or less. [2] The negative electrode for an all-solid-state secondary battery according to [1], wherein the negative electrode mixture layer is composed of two layers, namely, the first layer and the back surface layer. [3] The negative electrode for an all-solid-state secondary battery according to [1] or [2], wherein the negative electrode current collector is made of a metal, and the binder is a polyvinylidene fluoride polymer. [4] The negative electrode for an all-solid-state secondary battery according to any one of [1] to [3], wherein a peel strength between the negative electrode current collector and the negative electrode mixture layer is 35 mN / mm or more and 490 mN / mm or less. [5] An all-solid-state secondary battery comprising: a positive electrode; a negative electrode; and a solid electrolyte layer disposed between the positive electrode and the negative electrode, the negative electrode being the negative electrode for an all-solid-state secondary battery according to any one of [1] to [4]. [6] A negative electrode current collector and a negative electrode mixture layer, The negative electrode mixture layer includes a first layer forming a surface of the negative electrode mixture layer facing the negative electrode current collector, and a second layer forming a surface opposite to the first layer, applying a first negative electrode slurry onto the negative electrode current collector and drying the first negative electrode slurry to form the first layer; and applying a second negative electrode slurry onto the formed first layer and drying the slurry to form the second layer. the first negative electrode slurry and the second negative electrode slurry contain a negative electrode active material, a carbon material, a binder, and a solvent, a content C of the binder in the first negative electrode slurry is 5 parts by mass or more and 20 parts by mass or less with respect to 100 parts by mass of a total mass of the negative electrode active material and the carbon material in the first negative electrode slurry, a content D of the binder in the second negative electrode slurry is 1 part by mass or more and 10 parts by mass or less with respect to 100 parts by mass of a total mass of the negative electrode active material and the carbon material in the second negative electrode slurry, A method for producing a negative electrode for an all-solid-state secondary battery, wherein the content C is greater than the content D, and the difference between the content C and the content D is in the range of 4 parts by mass to 19 parts by mass. Note that the terms "first" and "second" herein are used for the sake of convenience to distinguish between the respective components, and the terms "first" and "second" do not have any particular meaning in terms of order or other characteristics. Effect of the Invention

[0011] According to the present invention, short circuits are unlikely to occur even when rapid charging is performed, and the battery capacity can be maintained high even after repeated charge / discharge cycles. [Brief description of the drawings]

[0012] [Figure 1] FIG. 1 is a cross-sectional schematic diagram showing a structure of an all-solid-state secondary battery according to one embodiment of the present invention. [Diagram 2] FIG. 4 is a cross-sectional view illustrating a structure of an all-solid-state secondary battery according to another embodiment of the present invention. [Diagram 3] FIG. 4 is a cross-sectional view illustrating a structure of an all-solid-state secondary battery according to another embodiment of the present invention. [Figure 4] FIG. 1 is a cross-sectional schematic diagram showing a structure of an all-solid-state secondary battery according to one embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] Hereinafter, preferred embodiments of the present invention will be described in detail with reference to the accompanying drawings. In this specification and the drawings, components having substantially the same functional configurations are designated by the same reference numerals, and duplicated explanations will be omitted.

[0014] <1. Basic configuration of the all-solid-state secondary battery according to the present embodiment> The all-solid-state secondary battery according to this embodiment is an all-solid-state secondary battery 1 including a positive electrode 10, a negative electrode 20, and a solid electrolyte layer 30, as shown in FIG.

[0015] (1-1. Positive electrode) The positive electrode 10 includes a positive electrode current collector 11 and a positive electrode composite layer 12. Examples of the positive electrode current collector 11 include a plate-shaped or foil-shaped body made of indium (In), copper (Cu), magnesium (Mg), stainless steel, titanium (Ti), iron (Fe), cobalt (Co), nickel (Ni), zinc (Zn), aluminum (Al), germanium (Ge), lithium (Li), or an alloy thereof. The positive electrode current collector 11 may be omitted.

[0016] Positive electrode mixture layer 12 includes a positive electrode active material and a solid electrolyte. The solid electrolyte included in positive electrode 10 may be the same type of solid electrolyte as described in the section on solid electrolyte layer 30 or a different type of solid electrolyte as long as it is capable of conducting lithium ions.

[0017] The positive electrode active material may be any positive electrode active material that is capable of reversibly absorbing and releasing lithium ions.

[0018] For example, the positive electrode active material can be formed using lithium salts such as lithium cobalt oxide (hereinafter referred to as LCO), lithium nickel oxide, lithium nickel cobalt oxide, lithium nickel cobalt aluminum oxide (hereinafter referred to as NCA), lithium nickel cobalt manganate (hereinafter referred to as NCM), lithium manganate, lithium iron phosphate, nickel sulfide, copper sulfide, lithium sulfide, sulfur, iron oxide, vanadium oxide, etc. These positive electrode active materials may be used alone or in combination of two or more.

[0019] Further, the positive electrode active material preferably contains a lithium salt of a transition metal oxide having a layered rock salt structure among the lithium salts described above. Here, the "layered rock salt structure" refers to a structure in which oxygen atom layers and metal atom layers are alternately and regularly arranged in the <111> direction of the cubic rock salt structure, and as a result, each atomic layer forms a two-dimensional plane. The "cubic rock salt structure" refers to a sodium chloride type structure which is a kind of crystal structure, and specifically represents a structure in which face-centered cubic lattices formed by cations and anions are displaced from each other by 1 / 2 of the edge of the unit cell.

[0020] Examples of the lithium salt of a transition metal oxide having such a layered rock salt structure include, for example, LiNi x Co y Al z O2 (NCA), or LiNi x Co y Mn z O2 (NCM) (where 0 < x < 1, 0 < y < 1, 0 < z < 1, and x + y + z = 1), etc., lithium salts of ternary transition metal oxides.

[0021] When the positive electrode active material contains the lithium salt of the ternary transition metal oxide having the above-described layered rock salt structure, the energy density and thermal stability of the all-solid-state secondary battery 1 can be improved.

[0022] The positive electrode active material may be covered with a coating layer. Here, the coating layer of the present embodiment may be any known coating layer for the positive electrode active material of the all-solid-state secondary battery. Examples of the coating layer include, for example, Li2O-ZrO2 and the like.

[0023] Furthermore, when the positive electrode active material is formed of a lithium salt of a ternary transition metal oxide such as NCA or NCM and contains nickel (Ni) as the positive electrode active material, it is possible to increase the capacity density of the all-solid-state secondary battery 1 and reduce metal elution from the positive electrode active material in a charged state. As a result, the all-solid-state secondary battery 1 according to this embodiment can improve the long-term reliability and cycle characteristics in a charged state.

[0024] Here, examples of the shape of the positive electrode active material include particle shapes such as a perfect sphere and an oval sphere. The particle size of the positive electrode active material is not particularly limited, and may be within a range applicable to the positive electrode active material of a conventional all-solid-state secondary battery. The content of the positive electrode active material in the positive electrode 10 is also not particularly limited, and may be within a range applicable to the positive electrode of a conventional all-solid-state secondary battery.

[0025] In addition to the above-mentioned positive electrode active material and solid electrolyte, the positive electrode 10 may contain additives such as a conductive assistant, a binder, a filler, a dispersant, and an ion conductive assistant, as appropriate.

[0026] Examples of the conductive assistant that can be mixed with the positive electrode 10 include graphite, carbon black, acetylene black, ketjen black, carbon fiber, and metal powder. Examples of the binder that can be mixed with the positive electrode 10 include styrene butadiene rubber (SBR), polytetrafluoroethylene, polyvinylidene fluoride (PVdF), and polyethylene. Furthermore, examples of the filler, dispersant, ion conductive assistant, and the like that can be mixed with the positive electrode 10 include known materials that are generally used in electrodes of all-solid-state secondary batteries.

[0027] (1-2. Negative electrode) The negative electrode 20 includes a negative electrode current collector 21 and a negative electrode composite layer 22 laminated on the negative electrode current collector 21. The negative electrode current collector 21 is preferably made of a material that does not react with lithium, that is, does not form any alloy or compound with lithium. Examples of materials that constitute the negative electrode current collector 21 include copper (Cu), stainless steel, titanium (Ti), iron (Fe), cobalt (Co), and nickel (Ni). The negative electrode current collector is preferably made of a metal such as those described above.

[0028] Negative electrode mixture layer 22 contains a negative electrode active material, a carbon material, and a binder (binding agent). The negative electrode active material may, for example, be an alloy-forming element that forms an alloy or compound with lithium through an electrochemical reaction during charging. The alloying element may be at least one selected from the group consisting of gold, platinum, palladium, silicon, silver, aluminum, bismuth, tin, and zinc.

[0029] When one or more of gold, platinum, palladium, silicon, silver, aluminum, bismuth, tin, and zinc are used as the alloying element, the negative electrode active material is, for example, granular, and the particle size is preferably 4 μm or less, more preferably 300 nm or less. In this case, the characteristics of the all-solid-state secondary battery 1 are further improved. Here, the particle size of the negative electrode active material is determined by, for example, the median diameter (so-called D 50 ) can be used.

[0030] Examples of the carbon material include amorphous carbon such as carbon black and graphene. Examples of carbon black include acetylene black, furnace black, and ketjen black.

[0031] Examples of the binder include styrene butadiene rubber (SBR), polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, etc. The binder may be the same type as the binder in the positive electrode mixture layer 12 and the solid electrolyte layer 30, or may be a different type.

[0032] In addition to the above, negative electrode mixture layer 22 may appropriately contain additives used in conventional all-solid-state secondary batteries, such as a filler, a dispersant, an ion conductive agent, a solid electrolyte, and the like.

[0033] (1-3.Solid electrolyte layer) The solid electrolyte layer 30 is formed between the positive electrode 10 and the negative electrode 20 and includes a solid electrolyte.

[0034] The solid electrolyte is not particularly limited as long as it can be used in an all-solid-state secondary battery, for example, one containing a sulfide-based solid electrolyte material or one containing an oxide-based solid electrolyte material, etc. In the present embodiment, as an example, a powder-like solid electrolyte composed of a sulfide-based solid electrolyte material will be described.

[0035] Examples of the sulfide-based solid electrolyte material include Li2S-P2S5, Li2S-P2S5-LiX (X is a halogen element, such as I, Br, or Cl), Li2S-P2S5-Li2O, Li2S-P2S5-Li2O-LiI, Li2S-SiS2, and Li2 S -SiS2-LiI, Li2S-SiS2-LiBr, Li2S-SiS2-LiCl, Li2S-SiS2-B2S3-LiI, Li2S-SiS2-P2S5-LiI, Li2S-B2S3, Li2S-P2S5-Z m S n (m and n are positive numbers, Z is Ge, Zn or Ga), Li2S-GeS2, Li2S-SiS2-Li3PO4, Li2S-SiS2-Li p MO q(p and q are positive numbers, and M is any of P, Si, Ge, B, Al, Ga, and In). Here, the sulfide-based solid electrolyte material is produced by treating a starting material (e.g., Li2S, P2S5, etc.) by a melt quenching method, a mechanical milling method, or the like. In addition, after these treatments, a heat treatment may be further performed. The solid electrolyte may be amorphous, crystalline, or a mixture of both.

[0036] In addition, among the above-mentioned sulfide-based solid electrolyte materials, it is preferable to use a material containing sulfur and one or more elements selected from the group consisting of silicon, phosphorus, and boron as the solid electrolyte. This improves the lithium conductivity of the solid electrolyte layer 30, and improves the battery characteristics of the all-solid-state secondary battery 1. In particular, it is preferable to use a solid electrolyte containing at least sulfur (S), phosphorus (P), and lithium (Li) as constituent elements, and it is more preferable to use a solid electrolyte containing Li2S-P2S5 in particular.

[0037] Here, when using a sulfide-based solid electrolyte material containing Li2S-P2S5 to form the solid electrolyte, the mixture molar ratio of Li2S and P2S5 may be selected, for example, in the range of Li2S:P2S5=50:50 to 90:10.

[0038] The solid electrolyte layer 30 may further contain a binder, and examples of the binder include styrene butadiene rubber (SBR), polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, etc. The binder in the solid electrolyte layer 30 may be the same as or different from the binder in the positive electrode mixture layer 12 and the negative electrode mixture layer 22.

[0039] (1-4. Relationship between charge capacity of positive and negative electrodes) The all-solid-state secondary battery 1 according to this embodiment is preferably configured so that the ratio of the charge capacity of the positive electrode mixture layer 12 to the charge capacity of the negative electrode mixture layer 22, i.e., the capacity ratio, satisfies the requirement of the following mathematical formula (1). 0.01 a: Charging capacity of the positive electrode mixture layer 12 (mAh) b: Charging capacity of negative electrode mixture layer 22 (mAh) The charge capacities of positive electrode mixture layer 12 and negative electrode mixture layer 22 can be measured by a measurement using an all-solid-state half cell.

[0040] As described above, in the all-solid-state secondary battery 1 according to this embodiment, it is preferable that the charge capacity of the positive electrode mixture layer 12 is excessively large relative to the charge capacity of the negative electrode mixture layer 22, and the all-solid-state secondary battery 1 is charged beyond the charge capacity of the negative electrode mixture layer 22. That is, it is preferable to overcharge the negative electrode mixture layer 22. In this case, lithium is absorbed in the negative electrode mixture layer 22 at the beginning of charging. That is, the negative electrode active material forms an alloy with the lithium ions that have moved from the positive electrode 10. When further charging is performed beyond the capacity of the negative electrode mixture layer 22, as shown in FIG. 2 or FIG. 3, lithium is precipitated on the back side of the negative electrode mixture layer 22, that is, between the negative electrode current collector 21 and the negative electrode mixture layer 22 and / or inside the negative electrode mixture layer 22, and a lithium precipitate layer 23 is formed by this lithium. The lithium precipitate layer 23 is mainly composed of lithium (mainly metallic lithium) although it contains a small amount of elements other than lithium.

[0041] This phenomenon occurs when the negative electrode active material contains a specific substance, i.e., an alloying element that forms an alloy or compound with lithium. During discharge, lithium in the negative electrode mixture layer 22 and the lithium deposit layer 23 is ionized and moves to the positive electrode 10. ​Therefore, in the all-solid-state secondary battery 1 according to this embodiment, the precipitated lithium can be used as the negative electrode active material. Furthermore, since the negative electrode mixture layer 22 covers the lithium precipitate layer 23, it functions as a protective layer for the lithium precipitate layer 23 and can suppress the precipitation and growth of dendrites. This suppresses short circuits and capacity reduction of the all-solid-state secondary battery 1, and ultimately improves the characteristics of the all-solid-state secondary battery 1.

[0042] The thickness of the negative electrode mixture layer 22 is preferably within a range that satisfies the requirements of the above mathematical formula (1), and is preferably 1 μm or more and 20 μm or less, more preferably 1 μm or more and 10 μm or less. If the thickness of the negative electrode mixture layer 22 is 1 μm or more, the characteristics of the all-solid-state secondary battery 1 can be further improved. If the thickness of the negative electrode mixture layer 22 is 20 μm or less, the resistance value of the negative electrode mixture layer 22 can be kept small, and as a result, the characteristics of the all-solid-state secondary battery 1 can be further improved. The thickness of negative electrode mixture layer 22 described above can be estimated, for example, by assembling all-solid-state secondary battery 1, and observing the average thickness of the cross section after pressure molding with a scanning electron microscope (SEM).

[0043] <2. Characteristic configuration of the all-solid-state secondary battery according to the present embodiment> As shown in FIG. 4 , the all-solid-state secondary battery 1 according to this embodiment is characterized in that the binder content in the negative electrode mixture layer 22 is different between a first layer 221 forming a surface 22a of the negative electrode mixture layer 22 in contact with the negative electrode current collector 21 and a second layer 222 forming a surface 22b of the negative electrode mixture layer 22 in contact with the solid electrolyte layer 30.

[0044] In this embodiment, negative electrode mixture layer 22 is made up of two layers, that is, the first layer and the second layer. The first layer 221 and the second layer 222 each contain a negative electrode active material, a carbon material, and a binder. As described below, the first layer 221 and the second layer 222 each refer to an entire layer formed by applying and drying one type of slurry having a certain composition.

[0045] The weight of the negative electrode mixture layer 22 is 0.2 mg / cm 2 More than 2.5mg / cm 2 Preferably, it is 0.5 mg / cm or less. 2 More than 2.0mg / cm 2 More preferably, it is 0.8 mg / cm or less. 2 More than 1.5mg / cm 2 It is even more preferable that: The basis weight of the first layer 221 is, for example, 0.1 mg / cm 2 More than 1mg / cm 2 It is preferable that the concentration is 0.1 mg / cm or less. 2 More than 0.8mg / cm 2 More preferably, it is 0.1 mg / cm or less. 2 More than 0.5mg / cm 2 It is even more preferable that: The basis weight of the second layer 222 is, for example, 0.1 mg / cm 2 More than 1.5mg / cm 2 It is preferable that the concentration is 0.3 mg / cm or less. 2 More than 1.3mg / cm 2 More preferably, it is 0.5 mg / cm or less. 2 More than 0.9mg / cm 2 It is even more preferable that:

[0046] The content A of the binder in the first layer (hereinafter also referred to as the first content) is 5 parts by mass or more and 20 parts by mass or less with respect to 100 parts by mass of the total content of the negative electrode active material and the carbon material in the first layer. The first content is preferably 10 parts by mass or more and 18 parts by mass or less, and more preferably 12 parts by mass or more and 16 parts by mass or less.

[0047] On the other hand, the binder content B (hereinafter also referred to as the second content) in the other layer, i.e., the second layer forming the surface 22b of the negative electrode mixture layer 22 on the side in contact with the solid electrolyte layer 30, is 1 part by mass or more and 10 parts by mass or less with respect to 100 parts by mass of the total content of the negative electrode active material and the carbon material in the first layer. The second content is preferably 1 part by mass or more and 8 parts by mass or less, and more preferably 1 part by mass or more and 5 parts by mass or less.

[0048] Furthermore, the first content is greater than the second content, and the difference between the first content and the second content is 4 parts by mass or more and 19 parts by mass or less. The difference is preferably 6 parts by mass or more and 17 parts by mass or less, and more preferably 8 parts by mass or more and 15 parts by mass or less.

[0049] The peel strength between the negative electrode current collector 21 and the negative electrode composite layer 22 is preferably 35 mN / mm or more and 500 mN / mm or less, more preferably 50 mN / mm or more and 500 mN / mm or less, and even more preferably 100 mN / mm or more and 490 mN / mm or less. If it is difficult to measure this value, for example, the result of a peel test using Kapton tape described in the examples below may be used as an index. Specifically, in the peel test using Kapton tape, when the test is performed multiple times, the rate at which the negative electrode composite layer 22 peels off from the negative electrode current collector 21 is preferably 25% or less, more preferably 15% or less, and even more preferably no peeling at all.

[0050] <3. Method for manufacturing the all-solid-state secondary battery according to the present embodiment> Next, a method for manufacturing the all-solid-state secondary battery 1 according to this embodiment will be described. The all-solid-state secondary battery 1 according to this embodiment can be manufactured by manufacturing the positive electrode 10, the negative electrode 20, and the solid electrolyte layer 30, respectively, and then stacking the above layers.

[0051] (3-1. Positive electrode manufacturing process) First, a mixture of materials (positive electrode active material, solid electrolyte, binder, etc.) constituting positive electrode mixture layer 12 is processed into a sheet shape. The positive electrode composite sheet thus obtained is cut into an appropriate shape and laminated on a positive electrode current collector as a positive electrode composite layer material, and the resulting laminate is pressurized (for example, pressurized using hydrostatic pressure) to produce a positive electrode 10 including a positive electrode current collector and a positive electrode composite layer.

[0052] (3-2. Negative electrode manufacturing process) First, a slurry is prepared by adding the negative electrode composite layer materials (negative electrode active material, carbon material, binder, etc.) constituting the negative electrode composite layer 22 to a polar solvent or a non-polar solvent. Next, the obtained slurry is applied onto the negative electrode current collector 21 and dried. Next, the obtained laminate is pressed (for example, pressurized using hydrostatic pressure) to prepare the negative electrode 20. The pressurizing step may be omitted. Note that the negative electrode 20 may be prepared by a method in which the negative electrode composite layer 22 is separately formed, and then laminated on the negative electrode current collector 21 and pressed.

[0053] In this embodiment, two types of slurries were used in the process of applying and drying the slurry on the negative electrode current collector 21. One of the two types of slurries (first slurry) was adjusted so that the binder content C was 5 parts by mass or more and 20 parts by mass or less with respect to 100 parts by mass of the total mass of the negative electrode active material and the carbon material in the layer obtained after applying and drying the first slurry and removing the solvent. The other (second slurry) was adjusted so that the binder content D was 1 part by mass or more and 10 parts by mass or less with respect to 100 parts by mass of the total mass of the negative electrode active material and the carbon material after removing the solvent from the second slurry. The mass ratios of the negative electrode active material, the carbon material, and the binder added when adjusting the first slurry and the second slurry are directly reflected in the mass ratios of the negative electrode active material, the carbon material, and the binder in the layer obtained after removing the solvent. Furthermore, the binder content C in the first slurry is greater than the binder content D in the second slurry by 4 parts by mass or more and 19 parts by mass or less. The first slurry was applied to negative electrode current collector 21 and dried, and then the second slurry was applied thereon and dried to form negative electrode mixture layer 22 consisting of two layers with different binder contents.

[0054] (3-3. Solid electrolyte layer production process) The solid electrolyte layer 30 can be produced, for example, by the following procedure or steps. First, the starting material is treated by melt quenching or mechanical milling.

[0055] For example, when the melt quenching method is used, a sulfide-based solid electrolyte material can be produced by mixing a predetermined amount of starting materials (e.g., Li2S, P2S5, etc.), forming them into pellets, reacting them in a vacuum at a predetermined reaction temperature, and then quenching them. The reaction temperature of the mixture of Li2S and P2S5 is preferably 400°C to 1000°C, more preferably 800°C to 900°C. The reaction time is preferably 0.1 hours to 12 hours, more preferably 1 hour to 12 hours. The quenching temperature of the reactant is usually 10°C or less, preferably 0°C or less, and the quenching speed is usually about 1°C / sec to 10000°C / sec, preferably about 1°C / sec to 1000°C / sec.

[0056] In addition, when using the mechanical milling method, the sulfide-based solid electrolyte material can be produced by stirring and reacting the starting raw materials (e.g., Li2S, P2S5, etc.) using a ball mill or the like. Note that the stirring speed and stirring time in the mechanical milling method are not particularly limited, but the faster the stirring speed, the faster the production rate of the sulfide-based solid electrolyte material can be, and the longer the stirring time, the higher the conversion rate of the raw materials to the sulfide-based solid electrolyte material can be.

[0057] The mixed raw material obtained by the melt quenching method or the mechanical milling method is then heat-treated at a predetermined temperature and pulverized to produce a particulate solid electrolyte. If the solid electrolyte has a glass transition point, it may change from amorphous to crystalline by heat treatment.

[0058] Next, the solid electrolyte obtained by the above method can be formed into a film by a known film forming method such as an aerosol deposition method, a cold spray method, or a sputtering method to produce the solid electrolyte layer 30. The solid electrolyte layer 30 may be formed by pressing solid electrolyte particles alone. The solid electrolyte layer 30 may also be formed by mixing the solid electrolyte with a solvent and a binder, applying and drying the mixture, and applying pressure.

[0059] (3-4. Assembly process of all-solid-state secondary batteries) The positive electrode 10, the negative electrode 20, and the solid electrolyte layer 30 produced by the above-mentioned method may be laminated so that the solid electrolyte layer 30 is sandwiched between the positive electrode 10 and the negative electrode 20, and pressurized (for example, by applying pressure using hydrostatic pressure) to produce the all-solid-state secondary battery 1 according to this embodiment.

[0060] <4. Effects of this embodiment> According to the positive electrode for an all-solid-state secondary battery or the all-solid-state secondary battery according to the present embodiment, the binder content in the first layer 221 forming the surface 22a of the negative electrode mixture layer 22 on the negative electrode current collector 21 side and the second layer 222 forming the surface 22b of the negative electrode mixture layer 22 on the solid electrolyte layer 30 side is set to be in an appropriate range for each peel strength, so that even when rapid charging is performed, peeling of the negative electrode mixture layer 22 from the negative electrode current collector 21 can be suppressed within a range that does not hinder lithium deposition. In addition, the adhesion between the negative electrode mixture layer 22 and the solid electrolyte layer 30 can be increased. As a result, it is possible to provide an all-solid-state secondary battery 1 that is less likely to cause a short circuit that suppresses peeling due to internal stress accompanying short circuiting and cycle progression of the battery and improves the capacity retention rate, and that can maintain a high battery capacity even when charge / discharge cycles are repeated. Since the negative electrode mixture layer 22 has a two-layer structure, the manufacture of the negative electrode 20 and the all-solid-state secondary battery 1 can be made relatively simple.

[0061] <5. Other embodiments of the present invention>

[0062] Although the preferred embodiments of the present invention have been described in detail above with reference to the accompanying drawings, the present invention is not limited to such examples. For example, in the above-described embodiment, the negative electrode mixture layer 22 has a two-layer structure in which two types of slurries having different binder contents are applied twice, but it may also be made into a three-layer structure in which three or more types of slurries having different binder contents are applied three or more times. In addition, it is clear that a person with ordinary knowledge in the technical field to which the present invention pertains can think of various modified or altered examples within the scope of the technical ideas described in the claims, and these will naturally be understood to fall within the technical scope of the present invention. EXAMPLES

[0063] The all-solid-state secondary battery according to the present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. EXAMPLES

[0064] [Preparation of positive electrode layer] LiNi as a positive electrode active material 0.8 Co 0.15 A l0.05 O2(NCA) ternary powder, Li2S-P2S5 (80:20 mol %) amorphous powder as a sulfide-based solid electrolyte, and vapor-grown carbon fiber powder as a positive electrode layer conductive material (conductive additive) were weighed out in a mass ratio of 60:35:5 and mixed using a planetary centrifugal mixer. Next, a dehydrated xylene solution in which SBR was dissolved as a binder was added to this mixed powder so that the SBR content was 5.0 mass % relative to the total mass of the mixed powder, thereby preparing a primary mixed liquid. A suitable amount of dehydrated xylene was added to this primary mixture to adjust the viscosity, thereby preparing a secondary mixture. Furthermore, in order to improve the dispersibility of the mixed powder, zirconia balls with a diameter of 5 mm were put into the secondary mixed liquid so that the space, mixed powder, and zirconia balls each occupied 1 / 3 of the total volume of the kneading vessel. The tertiary mixed liquid thus produced was placed in a planetary centrifugal mixer and stirred at 3000 rpm for 3 minutes to produce a coating liquid for a positive electrode active material layer. Next, a 20 μm thick aluminum foil collector was prepared as a positive electrode collector, and the positive electrode collector was placed on a tabletop screen printer, and the positive electrode active material layer coating liquid was applied onto the sheet using a metal mask having a thickness of 200 μm. The sheet on which the positive electrode active material layer coating liquid was applied was then dried on a hot plate at 60° C. for 30 minutes, and then vacuum dried at 80° C. for 12 hours. This was punched into a rectangular plate shape with a Thomson blade to form a positive electrode active material layer on the positive electrode collector. The total thickness of the positive electrode collector and the positive electrode active material layer after drying was about 170 μm.

[0065] [Preparation of negative electrode] A stainless steel foil current collector having a thickness of 10 μm was prepared as a negative electrode current collector. To form the negative electrode, carbon was used, CB2 (Asahi Carbon, specific surface area 52 m 2 24g of carbon (100g, oil absorption 193ml / 100g), 8g of silver (60nm, Dowa), and 56g of a solution of PVdF (S5130, Solvay) dissolved in N-methylpyrrolidone (NMP) at a concentration of 8wt% as a binder were weighed out, and 90g of NMP was added, and a slurry 1 with a mass ratio of carbon / silver / binder = 75 / 25 / 14 was obtained using a planetary centrifugal mixer (THINKY). The viscosity of the slurry 1 was 10,000 mP.s, which was within the range where there were no problems in coating. Next, 24 g of the carbon, 8 g of the silver, and 14 g of the binder solution were weighed out, and 112 g of NMP was added and stirred in the same manner to obtain slurry 2 containing a mass ratio of carbon / silver / binder = 75 / 25 / 3.5. The viscosity of slurry 2 was 9,000 mP.s, which was within the range where no problems occurred in coating. The slurry 1 was applied to the current collector using an applicator and dried at 80°C for 10 minutes. A portion of the slurry was used for a peel test from the current collector foil, and the remaining portion was similarly coated with the slurry 2 and dried to obtain the target electrode plate. The total weight of the carbon, silver, and binder (i.e., the solid content of the negative electrode composite layer) was 0.5 mg / cm for both the first and second layers. 2 and the total negative electrode mixture layer is 1.0mg / cm 2 The electrode plate was vacuum dried at 103° C. for 12 hours, punched out to a predetermined size with a pinnacle die, and assembled into a battery.

[0066] [Preparation of solid electrolyte layer coating solution] A primary mixed slurry was produced by adding SBR binder dissolved in dehydrated xylene to the amorphous powder of Li2S-P2S5 (80:20 mol%) as a sulfide-based solid electrolyte so that the amount was 1 mass% relative to the solid electrolyte. Furthermore, a secondary mixed slurry was produced by adding an appropriate amount of dehydrated xylene and dehydrated diethylbenzene to this primary mixed slurry for viscosity adjustment. Furthermore, in order to improve the dispersibility of the mixed powder, zirconia balls with a diameter of 5 mm were put into the tertiary mixed slurry so that the space, mixed powder, and zirconia balls each occupied 1 / 3 of the total volume of the kneading vessel. The tertiary mixed liquid produced in this way was put into a planetary centrifugal mixer and stirred at 3000 rpm for 3 minutes to produce a solid electrolyte layer coating liquid.

[0067] [Preparation of solid electrolyte sheet] The prepared solid electrolyte layer coating solution was applied with a blade onto a PET film with a release-treated surface, and then dried on a hot plate at 40°C for 10 minutes, followed by vacuum drying at 40°C for 12 hours to obtain a solid electrolyte sheet. The thickness of the solid electrolyte layer after drying was approximately 42 μm. The dried solid electrolyte sheet was punched out with a Thomson blade and processed to the specified size.

[0068] [Fabrication of electrolyte negative electrode structure] A solid electrolyte sheet was placed on the surface of the negative electrode so that the solid electrolyte layer and the negative electrode were in contact with each other, and then the solid electrolyte sheet was placed on a 3 mm thick aluminum plate (supporting material) with a release film attached, and vacuum laminate packing was performed including the supporting material. The solid electrolyte layer (also called the SE layer) on the solid electrolyte sheet was integrated with the negative electrode by submerging it in a pressurized medium and performing a hydrostatic treatment (a compaction process using an isostatic press) at 50 MPa. This is called an electrolyte negative electrode structure.

[0069] [Preparation of all-solid-state secondary batteries] The electrolyte negative electrode structure was placed in the center of the aluminum laminate, and the positive electrode layer was placed on top of it so that it was at the center of the electrolyte negative electrode structure. This was vacuum degassed and sealed, placed on a 3 mm thick aluminum plate (support material) with a release film attached, and vacuum laminated and sealed twice. This was then submerged in a pressurized medium and subjected to hydrostatic pressure treatment (consolidation process using an isostatic press) at 490 MPa to obtain a single cell (single battery) of an all-solid-state secondary battery.

[0070] [Negative electrode peeling test] The electrode plate made of the negative electrode was cut to 5 cm x 20 cm, placed on a 3 mm thick aluminum plate (support material) with a release film attached, and vacuum laminated and sealed twice. It was submerged in a pressurized medium and subjected to hydrostatic pressure treatment (consolidation process by isostatic pressing) at 490 MPa. After the treatment, Kapton tape (1 cm x 5 cm, product number: 650S#25) was evenly applied to the electrode plate by pressing it at eight places using a metal roller weighing 2 kg, and then pulled up vertically by hand to check the state of separation of the mixture from the current collector. In addition, a 180-degree peel test was performed using a Shimadzu autograph tensile tester, and the peel strength was quantified. The solid electrolyte layer was placed on the electrode plate, the hydrostatic pressure treatment was performed, and a peel test of the solid electrolyte layer using Kapton tape was similarly performed. The results are shown in Table 1. The evaluation criteria are as follows. The unit of the binder content in Examples 1 to 7 and Comparative Examples 1, 2, 7, and 8 in Table 1, parts by mass, is based on 100 parts by mass of the total content of the negative electrode active material and the carbon material in the first or second layer. Since Comparative Examples 3 to 6 have only one negative electrode mixture layer, the unit of the binder content in Comparative Examples 3 to 6 in Table 1, parts by mass, is based on 100 parts by mass of the total content of the negative electrode active material and the carbon material in the negative electrode mixture layer. 1: No peeling 2: Only the solid electrolyte layer is peeled off from the negative electrode 3: The entire solid electrolyte layer and part of the negative electrode are peeled off. 4: The entire solid electrolyte layer and the entire negative electrode are peeled off.

[0071] [Cycle evaluation of all-solid-state secondary batteries] The fabricated all-solid-state secondary battery was connected to a charge / discharge device (Toyo Systems, TOSCAT) and a cycle test was performed at 45°C. The cells were charged and discharged at 0.33C (CCCV_0.1Ccut) / 0.33C (4.25V / 2.5V), and the ratio of the discharge capacity at 200 cycles to the initial discharge capacity of 100 was defined as the capacity retention rate, and comparisons were made. The results are shown in Table 1. EXAMPLES

[0072] An all-solid-state secondary battery was produced under the same conditions as in Example 1 except for the following process for producing the negative electrode. [Preparation of negative electrode] A stainless steel foil current collector having a thickness of 10 μm was prepared as a negative electrode current collector. To form the negative electrode, carbon was used, CB2 (Asahi Carbon, specific surface area 52 m 2 24g of carbon (1.0g / g, oil absorption 193ml / 100g), 8g of silver (60nm, Dowa), and 80g of a solution in which PVdF (S5130, Solvay) was dissolved in N-methylpyrrolidone (NMP) at a concentration of 8wt% as a binder were weighed out, and 64g of NMP was added, and a slurry 3 consisting of carbon / silver / binder = 75 / 25 / 20 in mass ratio was obtained using a planetary centrifugal mixer (THINKY). The viscosity of slurry 3 was 12,000 mP.s, which was within the range where there were no problems in coating. Next, 24 g of the carbon, 8 g of the silver, and 4 g of the binder solution were weighed out, and 122 g of NMP was added and stirred to obtain a slurry 4 having a mass ratio of carbon / silver / binder = 75 / 25 / 1. The viscosity of the slurry 4 was 9,000 mP.s, which was within the range where no problems occurred in coating. The slurry 3 was applied onto the current collector using an applicator, dried at 80°C for 10 minutes, and then the slurry 4 was applied thereon and dried to obtain the target electrode plate. The total weight of the carbon, silver, and binder was 0.5 mg / cm for both the first and second layers. 2 and 1.0 mg / cm for the entire negative electrode mixture layer. 2 It was. The electrode plate was vacuum dried at 103° C. for 12 hours, punched out to a predetermined size with a pinnacle die, and assembled into a battery. The produced all-solid-state secondary battery was subjected to a peeling test and cycle evaluation in the same manner as in Example 1. The results are shown in Table 1. EXAMPLES

[0073] An all-solid-state secondary battery was produced under the same conditions as in Example 1, except for the following negative electrode production process. [Preparation of negative electrode] A stainless steel foil current collector having a thickness of 10 μm was prepared as a negative electrode current collector. To form the negative electrode, carbon was used, CB2 (Asahi Carbon, specific surface area 52 m 2 40 g of a solution prepared by dissolving 24 g of carbon (1.0 g / g, oil absorption 193 ml / 100 g), 8 g of silver (60 nm, Dowa), and PVdF (S5130, Solvay) as a binder in N-methylpyrrolidone (NMP) at a concentration of 8 wt% was weighed out, and 92 g of NMP was added. Using a planetary centrifugal mixer (THINKY), slurry 5 was obtained with a mass ratio of carbon / silver / binder = 75 / 25 / 10. The viscosity of slurry 5 was 10,000 mP.s, which was within the range where there were no problems with coating. The slurry 5 was applied onto the current collector using an applicator and dried at 80°C for 10 minutes, and then the slurry 4 used in Example 2 was applied thereon and dried to obtain the target electrode plate. The total weight of the carbon, silver, and binder was 0.5 mg / cm for both the first and second layers. 2 and 1.0 mg / cm for the entire negative electrode mixture layer. 2 The electrode plate was vacuum dried at 103° C. for 12 hours, punched out to a predetermined size with a pinnacle die, and assembled into a battery. The produced all-solid-state secondary battery was subjected to a peeling test and cycle evaluation in the same manner as in Example 1. The results are shown in Table 1. EXAMPLES

[0074] An all-solid-state secondary battery was produced under the same conditions as in Example 1, except for the following negative electrode production process. [Preparation of negative electrode] A stainless steel foil current collector having a thickness of 10 μm was prepared as a negative electrode current collector. To form the negative electrode, carbon was used, CB2 (Asahi Carbon, specific surface area 52 m2 20 g of a solution prepared by dissolving 24 g of carbon (1000 g, oil absorption 193 ml / 100 g), 8 g of silver (60 nm, Dowa), and PVdF (S5130, Solvay) as a binder in N-methylpyrrolidone (NMP) at a concentration of 8 wt% was weighed out, and 112 g of NMP was added. Using a planetary centrifugal mixer (THINKY), slurry 6 was obtained with a mass ratio of carbon / silver / binder = 75 / 25 / 5. The viscosity of slurry 6 was 10,000 mP.s, which was within the range where there were no problems with coating. The slurry 6 was applied onto the current collector using an applicator and dried at 80°C for 10 minutes, and then the slurry 4 used in Example 2 was applied thereon and dried to obtain the target electrode plate. The total weight of the carbon, silver, and binder was 0.5 mg / cm for both the first and second layers. 2 and 1.0 mg / cm for the entire negative electrode mixture layer. 2 It was. The electrode plate was vacuum dried at 103° C. for 12 hours, punched out to a predetermined size with a pinnacle die, and assembled into a battery. The produced all-solid-state secondary battery was subjected to a peeling test and cycle evaluation in the same manner as in Example 1. The results are shown in Table 1. EXAMPLES

[0075] An all-solid-state secondary battery was produced under the same conditions as in Example 1, except for the following negative electrode production process. [Preparation of negative electrode] A stainless steel foil collector with a thickness of 10 μm was prepared as a negative electrode current collector. To form a negative electrode, the slurry 3 used in Example 2 was applied onto the current collector using an applicator, dried at 80° C. for 10 minutes, and then the slurry 5 used in Example 3 was applied thereon and dried to obtain a target electrode plate. The total weight of the carbon, silver, and binder was 0.5 mg / cm for both the first and second layers. 2 and 1.0 mg / cm for the entire negative electrode mixture layer. 2 The electrode plate was vacuum dried at 103° C. for 12 hours, punched to a predetermined size with a pinnacle die, and assembled into a battery. The produced all-solid-state secondary battery was subjected to a peeling test and cycle evaluation in the same manner as in Example 1. The results are shown in Table 1. EXAMPLES

[0076] An all-solid-state secondary battery was produced under the same conditions as in Example 1, except for the following negative electrode production process. [Preparation of negative electrode] A stainless steel foil collector with a thickness of 10 μm was prepared as a negative electrode current collector. To form a negative electrode, the slurry 1 used in Example 1 was applied to the current collector using an applicator, dried at 80° C. for 10 minutes, and then the slurry 5 used in Example 3 was applied thereon and dried to obtain a target electrode plate. The total weight of the carbon, silver, and binder was 0.5 mg / cm for both the first and second layers. 2 and 1.0 mg / cm for the entire negative electrode mixture layer. 2 The electrode plate was vacuum dried at 103° C. for 12 hours, punched out to a predetermined size with a pinnacle die, and assembled into a battery. The produced all-solid-state secondary battery was subjected to a peeling test and cycle evaluation in the same manner as in Example 1. The results are shown in Table 1. EXAMPLES

[0077] An all-solid-state secondary battery was produced under the same conditions as in Example 1, except for the following negative electrode production process. [Preparation of negative electrode] A stainless steel foil collector with a thickness of 10 μm was prepared as a negative electrode current collector. To form a negative electrode, the slurry 1 used in Example 1 was applied to the current collector using an applicator and dried at 80° C. for 10 minutes, and then the slurry 4 used in Example 2 was applied thereon and dried to obtain a target electrode plate. The total weight of the carbon, silver, and binder was 0.5 mg / cm for both the first and second layers. 2 and 1.0 mg / cm for the entire negative electrode mixture layer. 2 The electrode plate was vacuum dried at 103° C. for 12 hours, punched out to a predetermined size with a pinnacle die, and assembled into a battery. The produced all-solid-state secondary battery was subjected to a peeling test and cycle evaluation in the same manner as in Example 1. The results are shown in Table 1. EXAMPLES

[0078] An all-solid-state secondary battery was produced under the same conditions as in Example 1, except for the following negative electrode production process. [Preparation of negative electrode] A 10 μm thick stainless steel foil current collector was prepared as the negative electrode current collector. The total weight of carbon, silver, and binder was 0.1 mg / cm for the first layer. 2 , the second layer is 0.9 mg / cm 2 Except for the above, the preparation was carried out in the same manner as in Example 1. The produced all-solid-state secondary battery was subjected to a peeling test and cycle evaluation in the same manner as in Example 1. The results are shown in Table 1. EXAMPLES

[0079] An all-solid-state secondary battery was produced under the same conditions as in Example 1, except for the following negative electrode production process. [Preparation of negative electrode] A 10 μm thick stainless steel foil current collector was prepared as the negative electrode current collector. The total weight of carbon, silver, and binder was 0.4 mg / cm for the first layer. 2 , the second layer is 0.6 mg / cm 2 Except for the above, the preparation was carried out in the same manner as in Example 1. The produced all-solid-state secondary battery was subjected to a peeling test and cycle evaluation in the same manner as in Example 1. The results are shown in Table 1. EXAMPLES

[0080] An all-solid-state secondary battery was produced under the same conditions as in Example 1, except for the following negative electrode production process. [Preparation of negative electrode] A 10 μm thick stainless steel foil current collector was prepared as the negative electrode current collector. The total weight of carbon, silver, and binder was 0.9 mg / cm for the first layer. 2 , the second layer is 0.1 mg / cm 2 Except for the above, the preparation was carried out in the same manner as in Example 1. The produced all-solid-state secondary battery was subjected to a peeling test and cycle evaluation in the same manner as in Example 1. The results are shown in Table 1.

[0081] An all-solid-state secondary battery was produced under the same conditions as in Example 1, except for the following negative electrode production process. [Preparation of negative electrode] A stainless steel foil collector with a thickness of 10 μm was prepared as a negative electrode current collector. To form a negative electrode, the slurry 2 used in Example 1 was applied to the current collector using an applicator and dried at 80° C. for 10 minutes, and then the slurry 1 used in Example 1 was applied thereon and dried to obtain a target electrode plate. The total weight of the carbon, silver, and binder was 0.5 mg / cm for both the first and second layers. 2 and 1.0 mg / cm for the entire negative electrode mixture layer. 2 The electrode plate was vacuum dried at 103° C. for 12 hours, punched out to a predetermined size with a pinnacle die, and assembled into a battery. The produced all-solid-state secondary battery was subjected to a peeling test and cycle evaluation in the same manner as in Example 1. The results are shown in Table 1.

[0082] An all-solid-state secondary battery was produced under the same conditions as in Example 1, except for the following negative electrode production process. [Preparation of negative electrode] A 10 μm thick stainless steel foil current collector was prepared as the negative electrode current collector. CB2 (Asahi Carbon, specific surface area 52 m) was used as carbon to form the negative electrode. 2 2 g of a solution prepared by dissolving 24 g of carbon (100 g, oil absorption 193 ml / 100 g), 24 g of silver (60 nm, Dowa) and 8 g of PVdF (S5130, Solvay) as a binder in N-methylpyrrolidone (NMP) at a concentration of 8 wt% was weighed out, and 122 g of NMP was added. Using a planetary centrifugal stirrer (THINKY), slurry 7 with a mass ratio of carbon / silver / binder = 75 / 25 / 0.5 was obtained. Slurry 7 had poor dispersibility and was in an agglomerated state. The slurry 6 used in Example 4 was applied to the current collector using an applicator, dried at 80° C. for 10 minutes, and then the slurry 7 was applied thereon. However, there was severe cohesion, and the desired electrode plate could not be obtained. Comparative Example 3

[0083] An all-solid-state secondary battery was produced under the same conditions as in Example 1, except for the following negative electrode production process. [Preparation of negative electrode] A stainless steel foil collector with a thickness of 10 μm was prepared as a negative electrode current collector. To form a negative electrode, the slurry 1 used in Example 1 was applied to the current collector using an applicator and dried to obtain a target electrode plate. The total weight of carbon, silver, and binder was 0.5 mg / cm for both the first and second layers. 2 and 1.0 mg / cm for the entire negative electrode mixture layer. 2 The electrode plate was vacuum dried at 103° C. for 12 hours, punched out to a predetermined size with a pinnacle die, and assembled into a battery. The produced all-solid-state secondary battery was subjected to a peeling test and cycle evaluation in the same manner as in Example 1. The results are shown in Table 1. Comparative Example 4

[0084] An all-solid-state secondary battery was produced under the same conditions as in Example 1, except for the following negative electrode production process. [Preparation of negative electrode] A 10 μm thick stainless steel foil current collector was prepared as the negative electrode current collector. CB2 (Asahi Carbon, specific surface area 52 m) was used as carbon to form the negative electrode. 2 100 g of a solution prepared by dissolving 24 g of carbon (1000 g), oil absorption 193 ml / 100 g), 8 g of silver (60 nm, Dowa) and PVdF (S5130, Solvay) as a binder in N-methylpyrrolidone (NMP) at a concentration of 8 wt% was weighed out, and 20 g of NMP was added. A slurry 8 consisting of carbon / silver / binder = 75 / 25 / 25 in mass ratio was obtained using a planetary centrifugal mixer (THINKY). The viscosity of slurry 8 was 15,000 mP.s, which was within the range where no problems occurred in coating. The slurry 8 was applied onto the current collector using an applicator and dried at 80° C. for 10 minutes to obtain the target electrode plate. The total weight of the carbon, silver, and binder was 0.5 mg / cm for both the first and second layers. 2 and 1.0 mg / cm for the entire negative electrode mixture layer. 2 The electrode plate was vacuum dried at 103° C. for 12 hours, punched out to a predetermined size with a pinnacle die, and assembled into a battery. The produced all-solid-state secondary battery was subjected to a peeling test and cycle evaluation in the same manner as in Example 1. The results are shown in Table 1. Comparative Example 5

[0085] An all-solid-state secondary battery was produced under the same conditions as in Example 1, except for the following negative electrode production process. [Preparation of negative electrode] A 10 μm thick stainless steel foil current collector was prepared as the negative electrode current collector. CB2 (Asahi Carbon, specific surface area 52 m) was used as carbon to form the negative electrode. 2 28 g of a solution prepared by dissolving 24 g of carbon (1.0 g / g, oil absorption 193 ml / 100 g), 8 g of silver (60 nm, Dowa), and PVdF (S5130, Solvay) as a binder in N-methylpyrrolidone (NMP) at a concentration of 8 wt% was weighed out, and 102 g of NMP was added. Using a planetary centrifugal mixer (THINKY), slurry 9 was obtained with a mass ratio of carbon / silver / binder = 75 / 25 / 7. The viscosity was 11,000 mP.s, which was within the range where there were no problems with coating. Next, the slurry 9 was applied onto the current collector using an applicator and dried at 80° C. for 10 minutes. The total weight of the carbon, silver, and binder was 0.5 mg / cm for both the first and second layers. 2 and 1.0 mg / cm for the entire negative electrode mixture layer. 2 The electrode plate was vacuum dried at 103° C. for 12 hours, punched out to a predetermined size with a pinnacle die, and assembled into a battery. The produced all-solid-state secondary battery was subjected to a peeling test and cycle evaluation in the same manner as in Example 1. The results are shown in Table 1. Comparative Example 6

[0086] An all-solid-state secondary battery was produced under the same conditions as in Example 1, except for the following negative electrode production process. [Preparation of negative electrode] A stainless steel foil collector having a thickness of 10 μm was prepared as a negative electrode current collector. The slurry 2 used in Example 1 was applied onto the current collector using an applicator and dried at 80° C. for 10 minutes to obtain a target electrode plate. The total weight of carbon, silver, and binder was 0.5 mg / cm for both the first and second layers. 2 and 1.0 mg / cm for the entire negative electrode mixture layer. 2 The electrode plate was vacuum dried at 103° C. for 12 hours, punched out to a predetermined size with a pinnacle die, and assembled into a battery. The produced all-solid-state secondary battery was subjected to a peeling test and cycle evaluation in the same manner as in Example 1. The results are shown in Table 1. Comparative Example 7

[0087] An all-solid-state secondary battery was produced under the same conditions as in Example 1, except for the following negative electrode production process. [Preparation of negative electrode] A stainless steel foil collector with a thickness of 10 μm was prepared as a negative electrode current collector. The slurry 9 used in Example 1 was applied to the current collector using an applicator, dried at 80° C. for 10 minutes, and then the slurry 6 was applied thereon and dried to obtain a target electrode plate. The total weight of the carbon, silver, and binder was 0.5 mg / cm for both the first and second layers. 2 and 1.0 mg / cm for the entire negative electrode mixture layer. 2 The electrode plate was vacuum dried at 103° C. for 12 hours, punched out to a predetermined size with a pinnacle die, and assembled into a battery. The produced all-solid-state secondary battery was subjected to a peeling test and cycle evaluation in the same manner as in Example 1. The results are shown in Table 1. Comparative Example 8

[0088] An all-solid-state secondary battery was produced under the same conditions as in Example 1, except for the following negative electrode production process. [Preparation of negative electrode] A 10 μm thick stainless steel foil current collector was prepared as a negative electrode current collector. Using an applicator, the slurry 3 was applied onto the current collector and dried at 80° C. for 10 minutes, and then the slurry 7 was applied thereon and dried to obtain the target electrode plate. The total weight of the carbon, silver, and binder was 0.5 mg / cm for both the first and second layers. 2 and 1.0 mg / cm for the entire negative electrode mixture layer. 2 The electrode plate was vacuum dried at 103° C. for 12 hours, punched out to a predetermined size with a pinnacle die, and assembled into a battery. The produced all-solid-state secondary battery was subjected to a peeling test and cycle evaluation in the same manner as in Example 1. The results are shown in Table 1.

[0089] [Table 1]

[0090] [Consideration] In Examples 1 to 10, the negative electrode mixture layer did not peel off from the negative electrode current collector foil, and the solid electrolyte layer did not peel off from the negative electrode mixture layer. In addition, the number of short circuits was all sufficiently low at 0 or 1, and the battery cycle evaluation showed a sufficiently high cycle retention rate of more than 80%.

[0091] The first layer has a basis weight of 0.9mg / cm 2 The weight of the second layer was increased to 0.1mg / cm 2 From a comparison of the results of Example 10, in which the weight of the first layer was reduced to 10, with the results of Examples 1, 8, and 9, it was found that a smaller weight of the first layer facilitates the diffusion of lithium and its deposition on the current collecting foil, resulting in better capacity retention and battery characteristics.

[0092] In contrast, in Comparative Example 1, in which the binder content of Example 1 was reversed, the binder content in the first layer was 3.5 parts by mass, so the peel strength between the negative electrode current collector and the negative electrode composite layer was small, resulting in a high probability of peeling between them. In addition, the binder content in the second layer was 14 parts by mass, so the binder covered the carbon material in the negative electrode composite layer, resulting in insufficient adhesion between the negative electrode current collector and the negative electrode composite layer. It is believed that the adhesion at the interface between the negative electrode composite layer and the solid electrolyte layer is mainly due to physical adhesion that occurs when the solid electrolyte layer, which has a relatively soft nature, bites into the fine irregularities formed on the surface of the negative electrode composite layer, which is formed by fixing and solidifying the particulate material with the binder, by pressure. Therefore, if the irregularities are filled by the binder and the contact area becomes small, the adhesion decreases. As a result, the number of battery short circuits was high at 7 out of 10, and the capacity retention rate was low at 65%.

[0093] In Comparative Example 3, the binder content was uniformly 14 parts by mass throughout the negative electrode mixture layer, ensuring sufficient peel strength between the negative electrode current collector and the negative electrode mixture layer, but on the other hand, the amount of binder covering the carbon in the negative electrode layer was large, so adhesion to the solid electrolyte layer was poor, and after hydrostatic pressure treatment, only the solid electrolyte peeled off at a high rate of 6 / 8. As a result, 50% of the batteries short-circuited, and the capacity retention rate was low at 81%.

[0094] In Comparative Example 4, the binder content was 25 parts by mass uniformly throughout the negative electrode mixture layer, resulting in excessive peel strength between the negative electrode current collector and the negative electrode mixture layer, while the amount of binder covering the carbon in the negative electrode mixture layer was large, resulting in poor adhesion to the solid electrolyte layer and only the solid electrolyte peeling off by 8 / 8 after hydrostatic pressure treatment. As a result, the deposition of lithium in the negative electrode was hindered, cracks occurred in the negative electrode mixture layer, and the battery was completely short-circuited early.

[0095] In Comparative Example 5, the binder content was uniformly 7.0 parts by mass throughout the entire negative electrode mixture layer, making it difficult to completely prevent peeling between the negative electrode current collector and the negative electrode mixture layer. In Comparative Example 6, the binder content was uniformly 3.5 parts by mass throughout the entire negative electrode mixture layer, and the peel strength between the solid electrolyte layer and the negative electrode mixture layer was sufficient in Comparative Example 6. Peeling occurred between the negative electrode current collector and the negative electrode mixture layer, resulting in a short circuit as in Comparative Example 5.

[0096] In Comparative Example 7, the binder content in the first layer was 7 parts by mass, and the adhesion between the negative electrode current collector and the negative electrode composite layer was sufficiently high. In addition, the binder content in the second layer was smaller than that of Comparative Example 5, and thus the balance was better than that of Comparative Example 5. However, since the difference in binder content between the first layer and the second layer was small at 2.0, short circuits occurred, albeit infrequently, and the capacity retention rate was also 80%.

[0097] In addition, in Comparative Example 8, in which the difference between the binder content of the first layer and the binder content of the second layer was large at 19.5, the occurrence rate of peeling and short circuiting was high. One of the reasons for this is thought to be that the binder content of the second layer was too low, which resulted in poor dispersion of the slurry, poor balance of the negative electrode mixture layer as a whole, and reduced binding strength.

[0098] From the above results, as shown in Examples 1 to 10, it was found that by setting the binder content A (first content) in the first layer to 5 parts by mass or more and 20 parts by mass or less with respect to 100 parts by mass of the total content of the negative electrode active material and the carbon material in the first layer, and the binder content B (second content) in the second layer to 1 part by mass or more and 10 parts by mass or less with respect to 100 parts by mass of the total content of the negative electrode active material and the carbon material in the second layer, the first content being greater than the second content, and the difference between the first content and the second content being in the range of 4 parts by mass or more and 19 parts by mass or less, a short circuit is less likely to occur during rapid charging and cycle deterioration can be suppressed. [Explanation of symbols]

[0099] 1 All-solid-state secondary battery 10 positive electrode 11 Positive electrode current collector 12 Positive electrode mixture layer 20 negative electrode 21 Negative electrode current collector 22 Negative electrode composite layer 221 1st layer 222 2nd layer 23 Lithium deposit layer 30 Solid electrolyte layer

Claims

1. A negative electrode for an all-solid-state secondary battery comprising a negative electrode current collector and a negative electrode mixture layer, the negative electrode mixture layer includes a first layer forming a surface of the negative electrode mixture layer facing the negative electrode current collector, and a second layer forming a surface of the negative electrode mixture layer opposite to the first layer, each of the first layer and the second layer contains a negative electrode active material, a carbon material, and a binder; a content A of the binder in the first layer is 5 parts by mass or more and 20 parts by mass or less with respect to 100 parts by mass of a total content of the negative electrode active material and the carbon material in the first layer, a content B of the binder in the second layer is 1 part by mass or more and 10 parts by mass or less with respect to 100 parts by mass of a total content of the negative electrode active material and the carbon material in the second layer, a negative electrode for an all-solid-state secondary battery, wherein the content A is greater than the content B, and a difference between the content A and the content B is in the range of 4 parts by mass or more and 19 parts by mass or less.

2. 2. The negative electrode for an all-solid-state secondary battery according to claim 1, wherein the negative electrode mixture layer is composed of two layers, the first layer and the second layer.

3. 2. The negative electrode for an all-solid-state secondary battery according to claim 1, wherein the negative electrode current collector is made of a metal, and the binder is a polyvinylidene fluoride-based polymer.

4. 2. The negative electrode for an all-solid-state secondary battery according to claim 1, wherein a peel strength between the negative electrode current collector and the negative electrode mixture layer is 35 mN / mm or more and 490 mN / mm or less.

5. An all-solid-state secondary battery comprising a positive electrode, a negative electrode, and a solid electrolyte layer disposed between the positive electrode and the negative electrode, the negative electrode being the negative electrode for an all-solid-state secondary battery according to any one of claims 1 to 4.

6. A negative electrode current collector and a negative electrode mixture layer, The negative electrode mixture layer includes a first layer forming a surface of the negative electrode mixture layer facing the negative electrode current collector, and a second layer forming a surface of the negative electrode mixture layer opposite to the first layer, applying a first negative electrode slurry onto the negative electrode current collector and drying the first negative electrode slurry to form the first layer; and applying a second negative electrode slurry onto the formed first layer and drying the slurry to form the second layer. the first negative electrode slurry and the second negative electrode slurry contain a negative electrode active material, a carbon material, a binder, and a solvent, a content C of the binder in the first negative electrode slurry is 5 parts by mass or more and 20 parts by mass or less with respect to 100 parts by mass of a total mass of the negative electrode active material and the carbon material in the first negative electrode slurry, a content D of the binder in the second negative electrode slurry is 1 part by mass or more and 10 parts by mass or less with respect to 100 parts by mass of a total mass of the negative electrode active material and the carbon material in the second negative electrode slurry, the content C is greater than the content D, and a difference between the content C and the content D is in the range of 4 parts by mass or more and 19 parts by mass or less.

Citation Information

Patent Citations

  • The Method for Preparing Electrodes and the Electrodes Prepared by Using the Same

    KR101527748B1

  • Multi-layer anode with Different Binder Content and Different Particle Size of Active Material in each layer and Lithium Secondary Battery Comprising the Same

    KR102053063B1

  • Multi-layer Electrode with Different Binder Content in each layer and Lithium Secondary Battery Comprising the Same

    KR102071585B1